Alcohol‐associated capillarization of sinusoids: A critique since the discovery by Schaffner and Popper in 1963. Issue 7 (23rd November 2021) - Mak, Ki M.; Kee, Dustin; Shin, Da Wi
Abstract: This article reviews the literature on capillarization of hepatic sinusoids since its discovery in 1963. Liver sinusoidal endothelial cells are uniquely fenestrated and lack an underlying basement membrane. In chronic liver disease, the sinusoids capillarize and transform into systemic capillaries, a process termed capillarization of sinusoids. The histopathology is marked by defenestration, basement membrane formation, and space of Disse fibrogenesis. Capillarized sinusoids compromise the bidirectional exchange of materials between sinusoids and hepatocytes, leading to hepatocellular dysfunction. Sinusoidal capillarization was first described in active cirrhosis of alcoholics in 1963. Since then, it has been found in early and progressive stages of alcoholic hepatic fibrosis before the onset of cirrhosis. The sinusoidal structure is not altered in alcoholic steatosis without fibrosis. Defenestration impairs the ability of the endothelium to filter chylomicron remnants from sinusoids into the Disse's space, contributing to alcohol‐induced postprandial hyperlipidemia and possibly atherosclerosis. Ethanol also modulates the fenestration dynamics in animals. In baboons, chronic alcohol consumption diminishes endothelial porosity in concomitance with hepatic fibrogenesis and in rats defenestrates the endothelium in the absence of fibrosis, and sometimes capillarizes the sinusoids. Acute ethanol ingestion enlarges fenestrations in rats and contracts fenestrations in rabbits. In sinusoidal endothelial cell culture, ethanol elicits fenestration dilation, which is likely related to its interaction with fenestration‐associated cytoskeleton. Ethanol potentiates sinusoidal injury caused by cocaine, acetaminophen or lipopolysaccharide in mice and rats. Understanding ethanol's mechanisms on pathogenesis of sinusoidal capillarization and fenestration dynamics will lead to development of methods to prevent risks for atherosclerosis in alcoholism.